Instagram Stories as a Creative Tool for Reviewing Students Writing - Lestari, Puji; Lilik Pujiani (Institut Agama Islam Negeri Palopo, 2024)
Writing is among the most challenging skills for most students, especially EFL students. Learning to write can be enjoyable if instructors employ diverse pedagogical techniques. Instagram is a digital medium that can assist students in enhancing their writing skills. This study examines the potential of Instagram as a tool for assessing students' writing abilities. The dataset was taken from the Management and Informatics classes from Horizon University Indonesia, together with relevant scientific literature. The author applied H. Douglas Brown and Heekyong Lee's Teaching by Principle theory for the analysis. The results indicate that the writing of Management and Informatics students involves specific grammatical errors. Nevertheless, it did not constrain their attempts to enhance their linguistic proficiency. Instagram may serve as one of the most engaging digital platforms for writing.